Gaya Hidup Komunitas Campervans di Bandung: Studi Kasus Komunikasi Lingkungan - Novianti, Felita Eka; Dirgantara, Pradipta (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Travel has evolved from mere tourism to mass tourism, focusing on leisure and recreational experiences. Nature-based tourism has become popular. Indonesia ranks 32 out of 117 in the Travel and Tourism Development Index, but limited accommodation options hinder its growth. The Ministry of Tourism plans to introduce campervans in 2022 to improve tourism quality. Therefore, research titled